Pneumoenphalus in semi-sitting position: prevalence, patterns and associated factors - RANC, Revista Argentina de Neurocirugia; Ulloque-Caamaño, Liezel; Zúñiga, Alexander (Revista Argentina de Neurocirugía, 2024)
Background. the semi-sitting position (SSP) in neurosurgery is controversial due to complications such as pneumocephalus (NE); however, it has benefits. Objectives: to analyze aspects of NE in patients with a variety of posterior fossa pathologies operated in a semi-sitting position. Methods: cross-sectional study. Patients with posterior fossa pathology operated in SSP, between January 2020 and June 2023. Demographic characteristics, type and location of the pathology, presurgical cerebrospinal fluid shunt, location and amount of cisternal opening, ventricular location and opening, surgical time, presence of NE, patterns and degrees, tension NE and neurological outcome were investigated. A p ≤0.05 value was shown to be significant. Results: 192 patients included. Age 47 ± 16.3 years, women 62.5%. NE 93.2%, no tension NE. NE subdural (87.5%), subarachnoid (66.6%), ventricular (15.6%). NE ˂40 years (86.4%), 40-60 (97.8%), ˃60 years (93.2%), p = 0.02. Age 40-60 years has 5.824 times more risk of presenting NE than ˂40 years (OR 6.824, 95% CI; 1.395-33.380, p=0.01). NE does not compromise the neurological outcome. Conclusions: the semi-sitting position has a high prevalence of postoperative NE with zero prevalence of tension NE; it is observed that the older the age, the greater the risk of NE. The use of PSS can be considered safe.